A biogeographical evaluation of high-elevation myxomycete assemblages in the northern Neotropics - Rojas Alvarado, Carlos Alonso (2011)
This study represented an effort to apply some of the relatively well-known biogeographical and macroecological models to the observed structure of myxomycete assemblages, with emphasis on the northern Neotropical region. A series of 28 experimental plots located in 14 study sites within five different countries was surveyed during two consecutive years using a standard methodology that included both field collections and specimens obtained from moist chamber cultures. Results showed that myxomycetes in high-elevation areas of the northern Neotropics seem to have different levels of preference for macro- and microenvironments, varying degrees of niche breadth and overlap, and different patterns of species occurrence in comparable areas. In a similar manner, species assemblages along a latitudinal gradient that extends from Mexico to Costa Rica showed a decreasing level of similarity with an assemblage studied in the temperate forests of the eastern United Stated and were clearly distinct from an assemblage in Thailand.